2022
DOI: 10.1186/s41983-022-00588-1
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrobasilar dolichoectasia in patients with cerebrovascular ischemic stroke: does it have a role in cerebral microbleeds?

Abstract: Background Vertebrobasilar dolichoectasia (VBD) may account for cerebral microbleeds (CMBs) in ischemic cerebrovascular stroke. Objectives To examine whether VBD is associated with the involvement of CMBs in any region and, if so, whether it is associated with CMBs among ischemic stroke patients located in posterior circulation territory. For patients with VBD, we also studied ischemic stroke subtypes, and checked whether dolichoectasia was linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…After removing duplicated records using an automation tool (The Systematic Review Accelerator: SRA) [ 27 ], abstract screening, and assessing 17 full texts, we included six case–control and observational cohort studies from seven publications comprising 6102 patients with ischaemic stroke (Fig. 1 ) [ 7 , 12 , 13 , 15 , 28 31 ]. Most of the included studies used computed tomography angiography (CTA) or magnetic resonance angiography (MRA) as imaging modalities for diagnosing IADE, however, in a study by Pico et al brain-autopsy was used, while the study of Brutto et al used a semiautomatic vessel calculation method, which IADE was performed using automated software, and used to calculate the vessel diameter, length and tortuosity index (TI) [ 12 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicated records using an automation tool (The Systematic Review Accelerator: SRA) [ 27 ], abstract screening, and assessing 17 full texts, we included six case–control and observational cohort studies from seven publications comprising 6102 patients with ischaemic stroke (Fig. 1 ) [ 7 , 12 , 13 , 15 , 28 31 ]. Most of the included studies used computed tomography angiography (CTA) or magnetic resonance angiography (MRA) as imaging modalities for diagnosing IADE, however, in a study by Pico et al brain-autopsy was used, while the study of Brutto et al used a semiautomatic vessel calculation method, which IADE was performed using automated software, and used to calculate the vessel diameter, length and tortuosity index (TI) [ 12 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The degree of basilar artery tortuosity, BA dolichosis, was independently associated with deep CMBs (Odds ratio (OR) 4.14, P = 0.002) [ 32 ]. In patients with VBD, CMBs are more frequently documented in the posterior circulation brain regions, including the cerebellum, thalamus, and occipital lobe [ 43 ] and a high CMBs burden (> 10 CMBs) was more frequent in vascular territories supplied by vessels arising from dolichoectatic vessels in the posterior region [ 31 ]. This anatomical link between large and small artery pathology is consistent with either shared pathophysiological mechanisms or vulnerability rather than simply shared risk factors [ 29 , 31 , 36 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It comprised up to 80% of intracranial arterial dolichoectasia. 2,3 It is discovered incidentally in 1.3-4.4% of general population and symptomatically in 7.6-18.8% of stroke population. Another report described that the incidence was 0.06-5.8%, but it contributes up to 12% cases of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Another report described that the incidence was 0.06-5.8%, but it contributes up to 12% cases of stroke. 2,3 While it may be asymptomatic, VBD may manifest in 46.8% subjects as vascular or compressive symptoms, including ischemic stroke, and subarachnoid hemorrhage, cranial nerve compression, brainstem compression, hydrocephalus, cerebellar dysfunction, and central sleep apnea. 1,4 Wolters et al studied 375 VBD subjects and reported that the 5-year new event included ischemic stroke (17.6%), brainstem compression (10.3%), transient ischemic attack (10.1%), spontaneous intracerebral hemorrhage (4.7%), hydrocephalus (3.3%), and subarachnoid hemorrhage (2.6%).…”
Section: Introductionmentioning
confidence: 99%